ChemInform Abstract: Chemoselective Deprotection of N‐Allylic Amines Using DDQ. Issue 18 (May 2015) - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu
Abstract The simple and mild method allows the deallylation of a wide variety of tertiary amines.